Personality of Ophelia in William Shakespeare's Hamlet (written about 1602/17th Century): a Psychoanalytic Approach - Prabawati, Aprillia, Drs. Abdillah Nugroho, M. Hum, Titis Setyabudi, S.S. M.Hum (2015)
The major issue of this study is "How is the personality of Ophelia reflected in William Shakespeare's Hamlet?" The objective of this study is to analyze the play based on its structural elements and psychoanalytic approach. The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. Primary data are taken from Hamlet play written by William Shakespeare. The secondary data sources are books and other data that have relationship with the research. The object of the study is the personality of Ophelia reflected in William Shakespeare's Hamlet. Technique of the data collection are reading the drama script, taking important note in both primary and secondary data, identifying the topic of the play, and analyzing the data of the research based on Sigmund Freud's theory. And the technique of the data analysis is descriptive analysis. The results of the study show the id of Ophelia is a good daughter. It is shown when her father orders her to quit seeing Hamlet, she agrees, "I shall obey my Lord" (H. Act 1, Sc 3). The ego of Ophelia appears in a condition where Ophelia tries to show her cares to her lord Hamlet. Through a song she tells that no one can make the same thing of love like Hamlet," How should I your true love know, from another one? By his cockle hat and staff, and his sandal soon" (H. Act 4, Sc 5). The superego of Ophelia appears in this script, where she tries to make a positive thinking related with the decision of Hamlet when he falls in love with her. The power of Ophelia in superego takes her mind to the positive way related with Hamlet's love.